2013
DOI: 10.4236/jep.2013.411144
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Nickel and Chromiumin Sediments in the Juru River, Penang, Malaysia

Abstract: Study was conducted to determine the concentrations of (Ni) and (Cr) in sediment and to investigate the effect pH and organic matters on concentrations of nickel and chromium in sediment at Juru River, Penang, Malaysia. The sequential extraction procedure was used based on defined fractions: exchangeable, acid reduction, oxidation and residual. The concentrations of Ni and Cr in residual fraction were higher than the other fractions. In non-residual fractions, the concentration of heavy metals in organic matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In this study, pH value in point A and B are in the range of 7.1- 7.5 which shows the environment is in slightly alkaline condition. The pH condition was quite similar to the study done by Idris and Ahmad [8] which shows that Juru river sediment condition were also in slightly acidic to slightly alkaline condition which are due to the presence of heavy metals (nickel and chromium) in the sediment. Meanwhile, point C, D and E were exists in moderately alkaline environment since the pH range between 7.6-8.3 which the pH where not mainly altered by the waterways contaminants.…”
Section: Sediment Characteristicssupporting
confidence: 84%
“…In this study, pH value in point A and B are in the range of 7.1- 7.5 which shows the environment is in slightly alkaline condition. The pH condition was quite similar to the study done by Idris and Ahmad [8] which shows that Juru river sediment condition were also in slightly acidic to slightly alkaline condition which are due to the presence of heavy metals (nickel and chromium) in the sediment. Meanwhile, point C, D and E were exists in moderately alkaline environment since the pH range between 7.6-8.3 which the pH where not mainly altered by the waterways contaminants.…”
Section: Sediment Characteristicssupporting
confidence: 84%
“…The OM content in the sediment was between 38% and 45% for all six compartments. Remarkably, lower values in the range of 7% to 16% (Idriss & Ahmad, 2013) and even 0.1% to 2.8% (Ahmad et al, 2009) were reported in other Malaysian mangroves. Similar to this study, Maslennikova et al (2012) reported 50% to 33% of OM in Russian lake.…”
Section: Soil Texture and Ommentioning
confidence: 86%
“…The low water flow condition leads to sediments being suspended in water column to have more time to sink and redeposited at the bottom [20]. The consequences of river transportation were found in many rivers such as Klang River [20], Juru River, Malaysia [41] and Keelung River drainage basin, Taiwan [42] Furthermore, estuary has been well known as a settlement for sedimentation during tidal period and tends to have higher sedimentation rate [20,41].…”
Section: Ong Et Al: Determination Of Total Organic Carbon Concentratimentioning
confidence: 99%